Renal Manifestation in Patients with Primary Hyperparathyroidism: a Retrospective Analysis in a Tertiary Institute (Bangladesh Journal of Nuclear Medicine, 2018)
Objectives: The classical renal manifestations of primary hyperparathyroidism (PHPT) are nephrolithiasis and nephrocalcinosis. The presence of renal stone categorizes PHPT as symptomatic variant. The clinical profile of PHPT has changed in past few decades with decreased prevalence of renal stone disease with the introduction of widespread routine biochemical screening in normal subjects. In developing countries, PHPT is still a late diagnosed disorder and most of the patients are symptomatic at presentation. Presence of renal stone in PHPT patients is an absolute indication of parathyroidectomy, hence it is important to identify renal involvement in PHPT. The objective of the study is to determine the rate of renal manifestations in patients of biochemically primary hyperparathyroidism and compared to control group. This retrospective review was performed to determine whether the rate of nephrolithiasis and nephrocalcinosis is still high in the patients who underwent dual phase 99mTc sestamibi scan for PHPT at National Institute of Nuclear Medicine and Allied Sciences (NINMAS) compared to those not affected by the disorder.Patients and Methods: A total 149 patients (male 72 and female   77) and mean age 41 ± 14.73 years with PHPT were included in this study. All patients underwent dual phase 99mTc sestamibi parathyroid scan. Result of 99mTc sestamibi scan were divided into two groups. Group I represented positive scan and group II indicated negative scan respectively.Relevant clinical history, biochemical values including serum calcium level, serum parathormone (PTH) level and data on renal manifestations were recorded. The control group comprised of 650 subjects who had abdominal ultrasonography for various clinical conditions without any history of PHPT. Renal manifestations were compared between PHPT patients and the control group.Results: Among 149 patients, scan was positive in 54(36.2%) cases (group I) and scan was negative in 95(63.8%) cases (group II). In group I, renal manifestations were present in 20 cases and   absent in 34 cases. In group II, renal manifestations were present in 32 cases and were absent in 63 cases. Nephrolithiasis and nephrocalcinosis were present in 45(30.2%) and 7(4.7%) cases respectively in study population compared to 8(1.23%) persons of control group of 650 subjects. Pearson’s chi-square analysis showed that the difference in the rate of renal manifestations was significant (p < 0.001) between study population and control group. However, with in the study population the rate of renal manifestations between group I and group II was not significantly different (p = 0.137).Conclusion: This study showed eighteen fold increased renal manifestations in the patients with PHPT imaged for parathyroid gland compared to the subjects not affected by the disorder. Symptomatic variant of PHPT with renal manifestation was higher in this study compared to western countries. During parathyroid scanning in PHPT routine ultrasonographic evaluation of kidneys is necessary to exclude renal manifestation, even with negative parathyroid scan.Bangladesh J. Nuclear Med. 20(1): 32-36, January 2017